Ragam Khitobah Ta’tsiriyah: Sebuah Tela’ah Ontologis - Aang Ridwan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2011)
Khitobah Activity is one of da’wah form that posited urgent. As functional, the da’wah form take a model transmission and diffusion of up to date Islamic doctrine, follow manner of social dynamic and religious tradition of moslem society.  With that character, khitobah ta’tsiriyyah can develop  several model  and form varieties. At least, there are three forms, are: khitobah al-waqi’iyyah, khitobah walimah and khitobah almunadzomah. Khitobah al-waqi’iyyah is khitobah activity concern with the big days momentum of Islam history and national event. Khitobah walimah, concern with tasyakur bin ni’mah. Khitobah almunadzomah as done by DKM (The Mosque Posperity Broad), Majlis Ta’lim, Islamic Traditional School, Islamic Society Organization, and so on.